Application Of Sq3r Learning Model For Improving Student Learning Outcomes And Activities In Learning Bahasa Indonesia - Yusmi Yusmi (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: Does using SQ3R model can improve student learning result of SD N 30 Timbulun in Indonesian language lesson? Steps taken in using the SQ3R learning model? The location of this research is SD Negeri 30 Timbulun. Subjects and Characteristics of students. Improved subjects are Indonesian subjects, while the number of students who became the target of research in class I as many as 27 people consisting of 15 women and 12 men. This research is in the form of process (observation and field note) and result of test. Observation is used to get data about students in following the learning of Indonesian language. This research indicates that the application of SQ3R model can improve comprehension comprehension if applied properly and in accordance with the implementation stage. Implementation of SQ3R model that is not perfect, less improve student learning result read comprehension. This is seen in classroom action research in cycle I to cycle III. Based on the research objectives, it can be concluded that the efforts of teachers to apply SQ3R model in reading comprehension learning can improve students' understanding of the reading. the details are as follows. 1) Increased reading progress through SQ3R model, every cycle I average score 56,44%, cycle II average value 66,11%, cycle III achievement result 88,11%. 2) The atmosphere of teaching and learning process goes well. All students do the job actively. This is seen when students strive to implement the stages of the strategy. Students can mention things that are known to the topic topics, can recount in their own words as well as summarize the content of the reading. 3) Activity of students in learning to run well because of its motivation to learn.